LIXIVIAÇÃO DE HERBICIDAS COM ELEVADA SOLUBILIDADE EM DIFERENTES TIPOS DE SOLOS - Terao, Daniel; Hanna, Lorette G.; Deuber, Robert (REVISTA DE AGRICULTURA, 2020)
LIXIVIAÇÃO DE HERBICIDAS COM ELEVADA SOLUBILIDADE EM DIFERENTES TIPOS DE SOLOS